Spongillaflies (Neuroptera: Sisyridae) of North America with a key to the larvae and adults - Bowles, David E. (Zootaxa, 2006)
The distributions of the two genera (Climacia and Sisyra) and six species of spongillaflies known to occur in Canada, Mexico and the United States are reviewed and summarized. Several new and significant distribution records are presented for states or provinces in these countries. Species diagnoses and a revised, illustrated key to the third instar larvae and adults of all species are presented.